Effectiveness of Planned Teaching Program Regarding the Care of Children with Hearing Impairment among the Caretakers in Selected Schools of Sangli District in India - Kale, Aparna (International Journal of Nursing Research, 2023)
Aim: The aim of the study was to study the effectiveness of planned teaching program regarding the care of children with hearing impairment among the caretakers in selected schools of Sangli district in India. Background: Hearing impairment means that you cannot hear well out of one or both ears, or you cannot hear at all. Hearing loss can range from mild to severe. There can be mild, moderate, severe, or severe impairment. Hearing loss as a child is a huge burden and handicap. It hurts the child’s quality of life because the disability affects all parts of his or her development, either directly or indirectly. The results include not being able to understand speech sounds, which often means not being able to communicate verbally, a delay in learning a language, a delay in cognitive development, a disadvantage in economics and education, social isolation, and a stigma. Methodology: The research approach for this study is quantitative approach and purposive research design was used. The sample size consisted of 60 caretakers. Result: The 33.34% of caretakers were between 30 and 40 years, 63.34% of caretakers were undergraduates, place-wise 58.34% of caretakers were from urban, 61.66% of caretakers had previous knowledge. The preceding data show that caretakers who got planned training on hearingimpaired children had higher mean knowledge scores in post-test than pre-test. Thus, structured training on caring for hearing-impaired youngsters worked. Thus, alternate hypothesis wins over null hypothesis. Conclusion: The structured teaching on care of children with hearing impairment proved to be effective in delivering the knowledge. Hence, null hypothesis is rejected and alternative hypothesis is accepted.